Effect of African Walnut (Tetracarpidium conophorum) Seed Oil on 3-Methylcholanthrene-Induced Mammary Carcinogenesis and Expression of COX-2 and PPAR-ɣ in Female Wistar Rats (African Journal of Biomedical Research, 2022)
Breast cancer is a commonly diagnosed disease among women, and dietary lipids has been implicated in its incidence. This study investigated the effect of feeding African walnut seed oil (AWSO) on 3-methylcholanthrene (MCA) induced mammary cancer and expression of cyclooxygenase-2 (COX-2) and peroxisome proliferator activated receptor gamma (PPAR-ɣ) in female Wistar rats. AWSO was extracted with n-hexane in a Soxhlet apparatus and characterized by gas chromatography. Group A and B of 21 days old rats (15 each) were fed with diet containing 10% AWSO for 12 weeks. After 4 weeks of feeding, group A animals were administered MCA (250mg/kg) intraperitoneally. Another group (group C with 15 animals) was fed with diet containing no AWSO and administered MCA (250mg/kg) intraperitoneally after 4 weeks of feeding. Results revealed that animals fed with AWSO had lower tumor incidence (21.7%), tumor weight (1.22g) and tumor volume of 948mm3 compare to the animals not fed with AWSO (87.4%, 9.41g, 6281mm3, respectively. The expression of cyclooxygenase-2 was observed only in MCA treated animals and it was significantly less on AWSO fed group than on animals in group not fed with AWSO. The expression of PPAR-γ was significantly more on animals in group fed with AWSO than in group C (not fed with AWSO).  Histological analysis of carcinogenesis were significantly (P < 0.05) more rapid on animals not fed with AWSO.   Our results revealed that dietary AWSO reduce breast carcinogenesis induced by MCA.